Pengaruh Kompetensi Aparatur, Partisipasi Masyarakat, dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa Tirong - Riyani Riyani; Andi Patimbangi; Rahma Hidayati Darwis (Universitas Persada Indonesia YAI, 2026)
This articel aims to analyze the influence of apparatus competence, community participation, and the utilization of information technology on the accountability of village fund management in Tirong Village, Palakka District, Bone Regency. This research uses a quantitative associative method with a saturated sampling technique involving 56 respondents. Data were analyzed using multiple linear regression with SPSS version 26. The results indicate that apparatus competence, community participation, and information technology utilization have a positive and significant effect on village fund management accountability, both partially and simultaneously. These three variables contribute 72.1% to village fund management accountability, while the remaining is influenced by other factors outside the research model.